用于监测压力的方法和系统 (2020)
用于监测主体的压力水平的方法和系统。同时获得主体的心脏的心跳至心跳时间变化和每搏输出量变化，并且根据心跳至心跳时间变化和相对每搏输出量变化来确定压力水平指示。可以获得对压力水平的更加准确和可靠的估计。 Method and system for monitoring stress level of a subject. Beat-to-beat time variation and stroke volume variation of the heart a subject are obtained simultaneously, and a stress level indication is determined as a function of the beat-to-beat time variation and the relative stroke volume variation. More accurate and reliable estimates for stress level may be obtained.